UTILITY OF FIBEROPTIC BRONCHOSCOPY FOR RETRIEVAL OF ASPIRATED HEADSCARF PINS - Al-Azzawi, Ahmed Ibraheem Abbas (European Scientific Journal, ESJ, 2013)
Background: Tracheobronchial foreign body aspiration is a worldwide health problem which often results in life threatening complications. Headscarf pin aspiration is a common and unique form of foreign body aspiration among young Muslim women. Rigid bronchoscopy (RB) is considered the standard procedure for retrieval. Standard flexible bronchoscopy (FOB) is used increasingly in the treatment of tracheobronchial headscarf pins aspiration in adults. Aim: The aim of this study is to evaluate the utility (use) of FOB for the retrieval (extraction) of aspirated headscarf pins. Materials and Methods: Patients with the diagnosis of headscarf pin aspiration admitted to Sulaimanyah Teaching Hospital, department of cardiothoracic and vascular Surgery from January 2008 to September 2011 were included in the study. Standard FOB procedure using an oral approach with patient in recumbent position, under local anesthesia and conscious sedation was performed as the primary tool for retrieval. Results: A total of 20 cases were admitted during the study period. The mean age of the sample was 24 years (10-40 years).All patients presented with cough while two of them had hemoptysis (10%) and five had unilateral wheeze on chest auscultation (25%). The aspirated pin was successfully retrieved in 19/20 cases (95%) during the first attempt of FOB. However, FOB was not successful in 1/20 case (5%). The aspirated pin was successfully retrieved by RB under general anesthesia. Conclusions: FOB is a safe and successful method when performed by an experienced bronchoscopist, well educated staff, and at a well equipped bronchoscopy unit. Headscarf pin aspiration is a relatively common form of foreign body aspiration among young Muslim Iraqi women. It commonly occurs when women hold the pins in their teeth while wearing the hejaab and talking to others at the same time.